A one-step procedure for immobilising the thermostable carbonic anhydrase (SspCA) on the surface membrane of Escherichia coli - Sonia Del Prete; Rosa Perfetto; Mosè Rossi; Fatmah A. S. Alasmary; Sameh M. Osman; Zeid AlOthman; Claudiu T. Supuran; Clemente Capasso (Taylor & Francis Group, 2017)
The carbonic anhydrase superfamily (CA, EC 4.2.1.1) of metalloenzymes is present in all three domains of life (Eubacteria, Archaea, and Eukarya), being an interesting example of convergent/divergent evolution, with its seven families (α-, β-, γ-, δ-, ζ-, η-, and θ-CAs) described so far. CAs catalyse the simple, but physiologically crucial reaction of carbon dioxide hydration to bicarbonate and protons. Recently, our groups characterised the α-CA from the thermophilic bacterium, Sulfurihydrogenibium yellowstonense finding a very high catalytic activity for the CO2 hydration reaction (kcat = 9.35 × 105 s−1 and kcat/Km = 1.1 × 108 M−1 s−1) which was maintained after heating the enzyme at 80 °C for 3 h. This highly thermostable SspCA was covalently immobilised within polyurethane foam and onto the surface of magnetic Fe3O4 nanoparticles. Here, we describe a one-step procedure for immobilising the thermostable SspCA directly on the surface membrane of Escherichia coli, using the INPN domain of Pseudomonas syringae. This strategy has clear advantages with respect to other methods, which require as the first step the production and the purification of the biocatalyst, and as the second step the immobilisation of the enzyme onto a specific support. Our results demonstrate that thermostable SspCA fused to the INPN domain of P. syringae ice nucleation protein (INP) was correctly expressed on the outer membrane of engineered E. coli cells, affording for an easy approach to design biotechnological applications for this highly effective thermostable catalyst.